Tinjauan Kritis Politik Dinasti di Indonesia - Djoni Gunanto (Program Studi Administrasi Negara Universitas Serang Raya, 2020)
Abstract In the body of political parties in Indonesia, it cannot be denied that there are oligarchies that can affect the nomination and candidacy mechanisms so that they do not work as they should. nomination of candidates by political parties is often based on the wishes of the political party elite, not based on the quality and integrity of the candidates. Political dynasties strengthen networks of power from the regional to the central level, whose orientation is to maintain power within political parties. The purpose of this research is to reveal comprehensively about the developing political dynasties in Indonesia. This research method is a literature review study, by exploring legal products, journals, articles, and documents. The data collection technique is done by noting literature sources. The research analysis was carried out using a qualitative approach using the content analysis model. The results of the study, political dynasties in Indonesia were carried out in two ways: by design and by accident. The political dynasty by design has been around for a long time. Relatively, the network of familism in government is already strong, so that relatives who enter the government or participate in political contestation have been arranged in such a way as to engineer the success of their goals. As for the political dynasty by accident occurs in a situation of succession of government which suddenly nominates relatives to replace them in order to maintain informal power over their successors if they win in political contestation. Dynastic politics can actually be accepted and not questioned as long as the recruitment and selection system for candidates in political contestation in Indonesia runs fairly and professionally. Therefore, the determination of candidates or candidates in political contestation in Indonesia must be based on a meritocratic system, which gives more rights to anyone with good achievements and track records to occupy strategic seats in government. Keywords: Politics, Dynasty, Candidate, regional elections Abstrak Di tubuh partai politik di Indonesia tidak dapat dipungkiri adanya oligarki yang dapat mempengaruhi mekanisme pencalonan dan kandidasi sehingga tidak berjalan sebagaimana mestinya. pencalonan kandidat oleh partai politik seringkali seringkali berdasarkan keinginan elit partai politik, bukan berdasarkan kualitas dan integritas calon. Dinasti politik memperkuat jaringan kekuasaan mulai dari tingkat daerah hingga pusat, yang orientasinya mempertahankan kekuasaan dalam tubuh partai politik. Tujuan penelitian, ini untuk mengungkap secara komprehensif tentang dinasti politik yang berkembang di Indonesia. Metode Penelitian ini merupakan studi literature review, dengan menelusuri produk hukum, jurnal, artikel, dan dokumen-dokumen. Teknik pengumpulan data dilakukan dengan mencatat sumber literatur. Analisis penelitian dilakukan menggunakan pedekatan kualitatif dengan menggunakan model analisis isi. Hasil Penelitian, Dinasti politik di Indonesia dilakukan dengan dua cara: by design dan by accident. Dinasti politik by design telah terbentuk sejak lama. Secara relasi, jejaring familisme dalam pemerintahan sudah kuat, sehingga kerabat yang masuk dalam pemerintahan atau terjun dalam kontestasi politik sudah diatur sedemikian rupa untuk merekayasa keberhasilan tujuannya. Adapun dinasti politik by accident terjadi dalam situasi suksesi pemerintahan yang secara tiba-tiba mencalonkan kerabat untuk menggantikannya demi menjaga kekuasaan informal erhadap penggantinya jika menang dalam kontestasi politik Kesimpulan. Politik dinasti sejatinya bisa diterima dan tidak dipersoalkan selama dalam pelaksanaan sistem perekrutan dan pemilihan calon dalam kontestasi politik di Indonesia berjalan secara adil dan profesional. Oleh karenanya, penentuan calon atau kandidat dalam kontestasi politik di Indonesia harus didasarkan pada sistem meritokrasi, yakni memberikan hak lebih kepada siapapun yang memiliki prestasi dan track record yang baik untuk menduduki kursi-kursi strategis dalam pemerintahan. Kata Kunci: Partai, Politik, Dinasti, Kandidat, Pilkada